2015
DOI: 10.18052/www.scipress.com/ilcpa.58.122
|View full text |Cite
|
Sign up to set email alerts
|

Infrared, <sup>1</sup>H-NMR Spectral Studies of some Methyl 6-O-Myristoyl-α-D-Glucopyranoside Derivatives: Assessment of Antimicrobial Effects

Abstract: ABSTRACT.This study was carried out to regioselective myristoylation of methyl α-Dglucopyranoside (1) using the direct acylation method gave the corresponding methyl 6-Omyristoyl-α-D-glucopyranoside (2) in fair yield. A number of 2,3,4-tri-O-acyl derivatives (3-15) of this 6-O-substitution product using a wide variety of acylating agents were also prepared in order to obtain newer derivatives of synthetic and biological importance. The reaction conditions are reasonably simple and yields were very good. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…2) of methyl α-D-glucopyranoside (1) using some non-traditional acylating agents namely, 4-t-butylbenzoyl chloride, 2-chlorobenzoyl chloride, 4-chlorobenzoyl chloride and benzoyl chloride. According to the well-known method i.e., direct acylation method (Kawsar et al, 2015;Kabir et al, 2005b), two series ( Fig. 1 and 2) were synthesized using methyl α-D-glucopyranoside as the starting material.…”
Section: Results and Discussion Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…2) of methyl α-D-glucopyranoside (1) using some non-traditional acylating agents namely, 4-t-butylbenzoyl chloride, 2-chlorobenzoyl chloride, 4-chlorobenzoyl chloride and benzoyl chloride. According to the well-known method i.e., direct acylation method (Kawsar et al, 2015;Kabir et al, 2005b), two series ( Fig. 1 and 2) were synthesized using methyl α-D-glucopyranoside as the starting material.…”
Section: Results and Discussion Synthesismentioning
confidence: 99%
“…From our previous works (Kawsar et al, 2013a(Kawsar et al, , 2015Kabir et al, 2008Kabir et al, , 2009, it also observed that in many cases the combination of two or more acyl substituents in a single molecular framework enhances the biological profile manifold than their parent nuclei (Kabir et al, 2004(Kabir et al, , 2005aKawsar et al, 2012a). Encouraged by our own findings and also literature reports, it synthesized a series of methyl α-D-glucopyranoside (1) derivatives ( Fig.…”
Section: Introductionmentioning
confidence: 92%
“…A number of rarely used acylating agents were employed for this purpose (Scheme 2 and Table 1) and the physicochemical properties of the synthesized compounds were presented in the ( Table 2). The structure of the acylated products were ascertained by analyzing their FTIR and 1 H-NMR spectra [29]- [31]. In continuation of a project going on the carbohydrate and protein chemistry laboratory, we intended to prepare a series of uridine derivatives for use as test compounds for biological evaluation.…”
Section: Chemistrymentioning
confidence: 99%
“…By similar procedure, the lauroyl derivative (7) was obtained as semi-solid. The IR spectrum displayed absorption bands at 1758 cm Final confirmation of the structure of the compound 2 was provided by preparation of its 2,6-dichlorobenzoyl derivative (13). Reaction of compound 2 with 2,6-dichlorobenzoyl chloride in pyridine, as usual procedure gave the dichlorobenzoyl derivative (13) as pasty mass.…”
Section: Chemistry and Spectral Characterizationmentioning
confidence: 99%
“…11,12 Of these, a direct method has been found to be the most encouraging method for acylation of carbohydrates and nucleosides. 13 It was found from the literature survey that nitrogen, sulphur and halogen containing heterocyclic compounds showed marked antimicrobial activities.…”
Section: Introductionmentioning
confidence: 99%